Difructose anhydride III decreases body fat as a low-energy substitute or by decreasing energy intake in non-ovariectomized and ovariectomized female rats. Issue 7 (3rd July 2017) - Fujitani, Mina; Kishida, Taro; Shimizu, Emi; Ishikawa, Junji
Abstract: We evaluated the effects of difructose anhydride III (DFAIII) on body weights of ovariectomized rats, which are a good model for obesity by estrogen deficiency-induced overeating. Female rats (10 weeks old) were subjected to ovariectomy or sham operation and then fed with or without a diet containing 3% or 6% DFAIII for 33 days or pair-fed control diet during the same period. Rats fed DFAIII showed significantly decreased food intake, energy intake, body weight gain, body energy accumulation, and fat tissue weight than control group, regardless of ovariectomy. DFAIII may decrease body fat dependent of reduced food/energy intake. Compared with the respective pair feeding groups, rats fed DFAIII showed significantly decreased body energy and fat tissue weight, regardless of ovariectomy, suggesting its potential as a low-energy substitute for high-energy sweeteners. The low energy of DFAIII may contribute to decreased body fat, which may not be dependent on obesity. Abstract : :